New nonlinear model to determine Cgs and Cgd capacities of GaAs MESFET - Merabtine, N.; Amourache, S.; Saidi, Y.; Zaabat, M.; Kenzai, Ch. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
New nonlinear model for simulating physical and geometrical parameters to determine the junctions capacities of "the Gallium Arsenide Metal Semiconductor Field Effect Transistor" GaAs MESFET are represented in this paper. Non linear variations of the bias and gate-source and gate-drain capacities have been found. A simulated values show excellent agreement with experimental results.